Who’s Afraid of Genderfluid Turtles? Gender Trouble with Translating Medieval Animal Stories - Vukašinović, Milan; Hölzlhammer , Lilli (Tidskrift för litteraturvetenskap, 2023)
The Old Indian fable collection Panchatantra was first introduced to the Greco-Roman world in the eleventh century via Middle Persian and Arabic translations, under the Greek title Stephanites and Ichnelates. The first Greek version continued to be translated into various other languages over the centuries, from the thirteenth-century Old Slavonic Stefanid and Ihnilat, translated into modern Serbian as Stefanit and Ihnilat (1999). The extended second medieval Greek version had a myriad of translations as well, the most recent being the English 2022 edition of Animal Fables of the Courtly Mediterranean. Several translators over centuries navigated the ‘untranslatability’ of characters’ gender in this text, on the intersection of grammatical, social and ‘natural’ categories. Our inquiry raises questions of social and grammatical gender, across times and spaces, examining how human gender constructs are materialized in animal characters and narrated in diversely gendered languages. Querying the linguistic differences of gender, we compare stories of selected characters from three different fables in Greek, English, Old Slavonic, and Serbian versions, while also looking at the Arabic source text Kalila and Dimnah. In the case of the lion’s mother, translations avoid using a word for female lion while emphasizing her role as queen-dowager and mother at the cost of her animality. The story of the owls introduces different grammatical genders for the birds outside of the court, while the individual owl-ministers and their king have to be male. The most curious case is that of two turtles whose gender roles are firmly assigned in Arabic but become so fluid in Greek and Old Slavonic that the animals change gender mid-sentence. While the stories highlight historically contingent gender performativity, the fact that the modern translators impose stable gender and heterosexuality upon their characters, opens up the space for debate on (mis)interpretatinons of animal sexuality and the queering and worldmaking potential of translation.